Flotation Process of Lithium from a Pegmatite-type Lithium Ore in Southern Africa - Litao LI; Jiushuai DENG (Kuangchan zonghe liyong)
The primary lithium minerals in the ore are spodumene, lithium-bearing muscovite, and lepidolite, with small quantities of montebrasite, elbaite, and lithiophyllite. The gangue minerals primarily consist of feldspar and quartz. The Li2O in the raw ore is 1.60%, 72.71% of the lithium is present in the form of spodumene, 16.90% in the form of lepidolite, 2.91% in the form of lithium phosphate minerals such as montebrasite and lepidolite, and 7.48% as lithium mineral inclusions within quartz and feldspar. The recyclable lithium minerals primarily include lepidolite and spodumene. The floatability of lepidolite and spodumene is quite similar, and their floatability can be adjusted through the use of appropriate flotation collectors, regulators, and activators, allowing for the flotation of both lepidolite and spodumene concentrates. Using organic acid AS as the collector, sodium carbonate and sodium hydroxide as regulators, and calcium chloride as the activator, lepidolite concentrate with a Li2O grade of 2.92% and a recovery of 15.47%, as well as spodumene concentrate with a Li2O grade of 6.36% and a recovery of 71.20%, were obtained through a small-scale closed-circuit test. The total Li2O recovery was 86.67%, with a corresponding Li2O grade of 5.26%.